Public image of nursing in modern society: An evolving concept analysis - Ying Duan; Xianqiong Feng; Hengyi Xiao (Wiley, 2024)
Abstract Aims This study aimed to analyse the evolution of the public image of nursing in the context of the constantly developing nursing profession. Design The Rodger's evolving concept analysis was applied. Methods PubMed, CINAHL, Web of Science, Scopus, and ProQuest databases were searched for articles published between 1 January 2001, and 30 April 2022, using the search terms; "NURS * AND image". The selected literature was screened using Rodgers' evolutionary method to explore the attributes, antecedents and consequences of the concept. Results The defining attributes were identified as nursing (nursing as the collective object), public (public as the collective subject) and information (the medium of interaction between the collective subject and the collective object). Nursing elements were classified into intrinsic elements (professional spirit, professional knowledge and professional skills) and extrinsic (appearance, language and behaviour) elements. Public elements were further subcategorized into public categories (internal organizational public and external organizational public) and public perceptions (cognition, emotion and behavioural intention). The information elements are mainly classified as information generation, dissemination, identification, processing and judgement. The antecedents and consequences of the public perception of nursing were also identified. Conclusions The public image of nursing is dynamic and has evolved over time. Its dynamism and malleability imply that the traditional public image of nursing can be improved through targeted interventions in nursing practice, management and education. Implications for the Profession Identifying the antecedents and consequences associated with the public image of nursing will help the healthcare organizations adopt effective strategies to alleviate the shortage of the nursing workforce and promote the development of the nursing profession. No Patient or Public Contribution.